Thermo-Mechanical Behaviour of Ultrahigh Molecular Weight Polyethylene-Carbon Nanotubes Composites under Different Cooling Techniques - S. Kanagaraj (2011)
Ultrahigh molecular weight polyethylene (UHMWPE) is a unique polymer with outstanding physical and mechanical properties that makes it particularly attractive to fabricate the bearing surface for artificial joints. Despite the requirement of visco-elastic properties of the UHWMPE and its composites, the characterization of them has received relatively little attention. The objective of this work is concerned with the studies on visco-elastic behaviour of UHMWPE and nanocomposites, which were prepared at optimized ball milling time with different cooling techniques. It is observed that stiffness of the materials increases appreciably at 0.2wt.% CNTs with an increase of frequency till 30Hz which confirms the reinforcing effect of CNTs in composites. The loss modulus of the sample is observed to be converged at higher temperature irrespective of frequency. The damping effect of the sample could be kept within the limit of polymer at any frequency range when the temperature is low and it is also possible at any temperatures at higher frequencies except LN2 cooled sample. The relaxation fraction increases with an increase of temperature and decreases with an increase of frequency. It is concluded that air cooled sample could be used wherever modulus is the main criteria irrespective of temperature and frequency, LN2 cooled sample can be used where more damping is required and water cooled samples may be used where more strength and toughness are required.